Effects of Arbuscular Mycorrhizal (AM) Fungi on Essential Oil Content and Nutrients Uptake in Basil under Drought Stress (Journal of Medicinal Plants and By-products, 2014)
Study the effects of inoculation with two arbuscular mycorrhizal (AM) fungi, Gm (Glomus mosseae T.H. Nicolson & Gerd.)Gerd & Trappe) and Gi (Glomus intraradices  N.C. Schenck & G.S. Sm.) on the  herb yield, essential oil (EO) content and nutrient acquisition of basil (Ocimum basilicum L.) under drought stress conditions,The experiment conducted with 9 treatments and 4 replications. Drought stress treatments were applied by increasing the irrigation intervals from 4 days to 8 and 12 days. The root colonization, dry matter yield, oil content, oil yield and nutrients uptake decreased as the irrigation intervals increased. The AM fungi inoculation significantly increased the dry matter yield, oil content, oil yield and uptake of N, K, Zn, Fe and Cu as compared to Nm (non-mycorrhizal) plants in both well-watered and drought stressed condition. Analysis of essential oil by GC and GC/MS showed that Linalool, (E)-β-ocimene, eugenol and (Z, E)-farnesol, main components of oil, had no significant variation by drought stress or AM fungi inoculation. The effect of AM fungi inoculation on herb yield, oil content, oil yield and nutrient acquisition was more significant with G. mosseae than G. intraradices. Results suggest that inoculation of AM fungi could be a feasible procedure to increase growth, yield and essential oil production under water deficit conditions.